Like Father, Like Daughter (Unless There Is a Son): Sibling Sex Composition and Women's STEM Major Choice in College - Umut Oguzoglu; Serkan Ozbeklik (Institute for the Study of Labor (IZA), 2016)
We investigate the potential role of fathers in females' decision to choose a science, technology, engineering and mathematics (STEM) major in college. The main innovation of our paper is to analyze how sibling sex composition affects the probability of being a STEM major in college for females whose fathers are in a STEM occupation. Using the National Longitudinal Survey of Youth 1979 (NLSY79), we find that, for females, having brother(s) significantly decreases the likelihood of choosing a STEM major in college when their fathers are also in a STEM occupation. The inclusion of variables pertaining to respondents' attitudes toward traditional gender roles, birth order, and the presence of an older brother as well as frequently used cognitive skill measures does not change the results. Thus, the observed effect appears to be driven by change in the college major preferences of females. We replicate the analysis using a more recent data set from the U.S. and data from Australia, and find similar results. Our findings suggest that fathers are much more likely to transmit occupation-specific tastes and preferences to their daughters in the absence of a son potentially, contributing to the persistence of the gender gap in STEM majors in college.
Keywords: J24; J16; I23; 330; STEM; gender gap; college major; siblings sex composition; intergenerational transmission